2014
DOI: 10.3892/etm.2014.1641
|View full text |Cite
|
Sign up to set email alerts
|

Resolvin E1 reduces hepatic fibrosis in mice with Schistosoma japonicum infection

Abstract: The aim of this study was to investigate whether resolvin E1 (RvE1) protects against hepatic fibrosis in a murine model of liver fibrosis induced by Schistosoma japonicum infection. A total of 30 pathogen-free Kunming mice were randomly and equally divided into three groups: Control (uninfected, untreated), model (infected, untreated) and RvE1 intervention (infected, RvE1-treated; 100 ng daily). The mice were infected with Schistosoma japonicum by inoculating the abdominal skin with 20±2 cercariae to induce mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 19 publications
8
16
0
Order By: Relevance
“…Proteins HA, LN and PC III are important biomarkers of hepatic fibrogenesis [ 30 , 31 ]. Hydroxyproline in liver is an important index whose level reflects the amount of collagen and therefore it can be used to determine the extent of fibrosis [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Proteins HA, LN and PC III are important biomarkers of hepatic fibrogenesis [ 30 , 31 ]. Hydroxyproline in liver is an important index whose level reflects the amount of collagen and therefore it can be used to determine the extent of fibrosis [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Resolvins, a family of endogenous lipid mediators derived from ω-3 polyunsaturated fatty acid, has been generated from EPA and DHA of fish oil. This family of lipid mediators include resolvin E and D, showing obvious potency in treating hepatic fibrosis in mice with infection, liver cirrhosis or neurodegenerative disorders (11), especially for the disease conditions associated with inflammation. Importantly, various studies showed that resolvins have an ability to perform potent anti-inflammatory actions in obesity-induced liver disease (19).…”
Section: Discussionmentioning
confidence: 99%
“…Resolvins, an anti-inflammatory and endogenous lipid mediator family, have been reported to play an important role in the treatment of many diseases. Resolvin D1 and resolvin E1 (RvD1/RvE1) are compounds that are made by the human body from the ω-3 fatty acids eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) (9)(10)(11). They are increasingly and continuously generated by COX-2 pathway especially in the presence of aspirin.…”
Section: Introductionmentioning
confidence: 99%
“…A temporal lipid mediator class switch leads to the production of the LXs (34) and also involves phospholipases (35) and the Rvs, which give signals to macrophages and the nonphlogistic recruitment of monocytes (36,37), as they eat and take up the apoptotic neutrophils via phagocytosis (38). When added back pharmacologically, Rvs and other SPMs, such as the PDs regulate inflammatory mediators by counterregulation [TNFa, platelet activating factor (PAF), PGs, LTs, chemokines, and cytokines] to head off inflammation in animal models (see Table 2 for recent preclinical models) as well as organ fibrosis (39)(40)(41)(42). The MaRs and RvE1 were first recognized (43,44) to stimulate resolution, tissue regeneration, and subsequent wound healing (21,45).…”
Section: Alpha Signals Omega In the Cascadementioning
confidence: 99%